A new species of Tharybis (Crustacea: Copepoda: Calanoida: Tharybidae) from northern Taiwan - Wang, Yan-Guo; Hwang, Jiang-Shiou (Zootaxa, 2022)
A new species Tharybis kueishanensis sp. n. (Copepoda: Calanoida: Tharybidae) is described from the inshore surface waters of Kueishan Island off northern Taiwan, which is the first report of Tharybis from the China Seas. Its female is distinguished from the other species of Tharybis by the total body length (1.89–2.12 mm) larger than the other species, the shape of the genital double-somite, which is slightly asymmetrical with a small notch on the distal margin of the right side, and the length of the inner terminal spine of leg 5, which is about 1.5 times of the terminal spiniform projections. The male is distinguished by the presence of 3 triangular projections at the inner middle margin and the tip of the distal segment of the right leg 5.